STIGMA TERHADAP DISABILITAS DALAM KONTEKS SOSIAL DAN PENDIDIKAN INKLUSIF: TINJAUAN ANALITIS ATAS FAKTOR PENYEBAB, DAMPAK, DAN STRATEGI PENGURANGANNYA - Agnes M.V Beri Luky; Dinda N. Mella, Dyasandro E. Nitti, Enjelina Hauteas, Elsa Y. Manafe, Ernes Pahabol, Sandi Fallo, Yo (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
Stigma against disability remains a major obstacle to realizing a just and inclusive society. Stigma manifests not only in the form of negative labels but also in discriminatory practices that limit access for people with disabilities to education, employment, social participation, and public services. This article examines stigma against disability from a social and inclusive education perspective by examining its causes, impacts, and reduction strategies. In general, stigma develops through a lack of disability literacy, cultural influences, stereotypes about disability, and minimal equal interaction between the community and people with disabilities. In the educational context, stigma can reduce learning participation, trigger social isolation, and hinder the effective implementation of inclusive education. Through a literature review and conceptual analysis, this article demonstrates that stigma reduction requires multi-level interventions, ranging from public education and strengthening inclusive school policies, family involvement, to more equitable media representation. Inclusive education is understood not simply as the placement of students with disabilities in mainstream schools, but rather as a transformation of values, culture, and practices so that diversity is truly valued. Therefore, stigma reduction is a crucial prerequisite for creating an equitable, safe, and dignified educational ecosystem for all students.